“JANCOK": A Symbol of Popular Culture Identity Are'k Suroboyo Area in the Era of Digital Lifestyle - Hidajat, Koerniawan; Nathadiharja, Sri Sukartono (PRoMEDIA, 2024)
AbstractThe accelerated development of information and communication technology including computers has made people live a digital lifestyle. The practice of using social media as part of a digital lifestyle has consequences for the community's adaptation to the transformation of the community's communication culture, so that the penetration of cultural clashes and fusion cannot be avoided due to the acceleration of digital trends without limits. The purpose of writing the article is to provide a description of the phenomenon of using the word “Jancok” as a symbol of the identity of the Surabaya regional popular culture or “Arek Suroboyo” language on social media as a feature of the digital lifestyle. The method of writing the article is based on a literacy review descriptive phenomenological approach. The cultural identity of the “Arek Suroboyo” region is characterized by three parts of formal language, inter-group language applies between groups and Javanese dialect Suroboyo. Symbol of actualization: egalitarian, democratic and solidarity. The origin or history of the use of the word “Jancok” is divided into two versions: 1) a symbol of the spirit of struggle against Dutch colonization, until now still used to symbolize the spirit in Surabaya. 2) the scientific research version, developing the use of the word “Jancok” scientifically both in terms of its culture and language. “Jancok” in the digital lifestyle varies in writing, and its meaning makes multiple opinions on ideas to get comments. It shows familiarity in friendship and does not have negative connotations, the language analysis points to pragmatic elements of implicature, swearing elements of affection, Slank language, cultural penetration.Keywords: Jancok, Popular Culture, Language, Digital Lifestyle, Socialmedia AbstraksiPercepatan perkembangan tehnologi informasi dan komunikasi termasuk komputer menjadikan masyarakat bergaya hidup digital. Praktek penggunaan media sosial bagian gaya hidup digital, berkonsekuensi adaptasi masyarakat terhadap transformasi budaya komunikasi masyarakat, sehingga penetrasi benturan dan peleburan budaya tidak bisa di hindari akibat untuk memberikan deskripsi fenomena penggunaan kata “Jancok” sebagai simbol identitas budaya poluler daerah Surabaya atau bahasa “Arek Suroboyo” pada media sosial merupakan ciri gaya hidup digital. Metode penulisan artikel berdasar literasi review pendekatan deskriptif fenomenologi. Identitas budaya daerah “Arek Suroboyo” di tandai tiga bagian bahasa formal, bahasa antar kelompok berlaku antar kelompok dan bahasa Jawa dialek Suroboyo. Simbol aktualisasi: egaliter, demoratis dan solidaritas. Asal atau sejarah penggunaan kata “Jancok”, di bagi 2 versi: 1) simbol semangat perjuangan melawan penjajahan Belanda, sampai sekarang masih di pakai untuk simbol pemicu semangat di Surabaya. 2) versi penelusuran ilmiah, mengembangkan penggunaan kata “Jancok” secara ilmiah baik dari sisi kulturnya dan bahasanya. “Jancok” dalam gaya hidup digital bervariasi penulisan, dan maknanya menjadikan multi opini atas ide untuk mendapatkan komentar. Menunjukkan keakraban dalam pertemanan dan tidak berkonotasi negatif, sisi analisa bahasa menunjuk pragmatis unsur implikatur, segi umpatan unsur afeksi, bahasa slank, penetrasi budaya.Kata Kunci: Jancok, Budaya Populer, Bahasa, Gaya Hidup Digital, Media Sosial